Microplastic Contamination in Freshwater and Marine Ecosystems: Sources, Fate, and Ecological Impacts - Al-Masoud, Haya (International Journal of Aquatic Research and Environmental Studies, 2026)
The problem of microplastic pollution has now become an iconic force upon freshwater and marine environments as plastic debris is constantly broken down, moved, deposited, and biologically interacted with across linked aquatic environments. This narrative review is a synthesis of peer-reviewed information on the significant sources, environmental fate, and ecological effects of microplastics in rivers, lakes, estuaries, coastal waters, open oceans, sediments, and biota. This review states that microplastics cannot be considered as a homogenous contaminant, but rather a heterogeneous collection of particles that behave and pose risks in response to polymer chemistry, size, shape, density, weathering condition, additives, biofouling, and sorbed pollutants. The main input sources include land-based leakage, wastewater effluents, stormwater runoff, atmospheric deposition, textile fibers, packaging waste, and fishing related materials. Upon release, particles are transported redistribution by hydrodynamic transport, by sedimentation, by resuspension, by aggregation, by biofouling, by ingestion, by egestion, and by trophic interactions. The strongest evidence of ecological effects with respect to ingestion, feeding interference, oxidative stress, retarded growth, disturbed reproduction, and contaminant-vector mechanisms is provided by some experimental conditions. Nonetheless, interpretation of risk is limited by inconsistent sampling, detection limits of variables, lack of polymer confirmation and poor comparability of laboratory exposures with environmental concentrations. The review determines priority research requirements categorized into harmonized monitoring, freshwater sediment risk assessment, nanoplastic detection, chronic mixture toxicity and source-focused mitigation.
Keywords: Microplastics, freshwater ecosystems, marine pollution, ecological risk, bioaccumulation, wastewater, sediment